THE PROCESSES OF LAW ENFORCEMENT AND ADMINISTRATION OF JUSTICE: A CASE STUDY OF THE JUDICIARY IN THE WESTERN STATE OF NIGERIA (1976)
This is a study of judicial processes and procedure in the Western State of Nigeria. The judiciary is conceptualized as a formal organization which lacks fitness into the classical organizational theory of bureaucracy because it is engulfed in intra-organizational and inter-organizational complications. Judicial processes and procedure are therefore to be understood within the framework of a multi-organizational inter-connectedness. Consequently, the study took as its theoretical focus the systemic approach which in turn embraces the structural- functional orientation with the concomitant exchange and conflict under-pinnings. Its central focus is that organizational interdependence will affect organizational performance adversely or positively even if the rules of bureaucracy are observed. The study also examines the judiciary as a formal Organization in which professionalism encourages fragmentation of group cohesion and this, in turn, is shown to limit the degree of bureaucratization found in the Organization. The end result of these perspectives is that organizational performance is a function of the interaction of internal and external forces. Consequently, it is concluded that a combination of the natural and rational models to the study of organization would enhance our understanding of organizations and the judiciary in particular. This study is divided into three main perspectives. The first takes an historical orientation, tracing the development of the judiciary in Nigeria from its very inception through a period of institutional experimentation to a period of institutional stability and reforms. It also traced the circumstances which led to the regionalization of the judiciary in Nigeria and how the judiciary of the Western State of Nigeria has performed during periods of political instability and experimentation. This section also focuses on the jurisdictional limitations of the various tribunals and their relations with one another. The second part focuses on the internal organizational structure of the judicial departments and isolates the interaction of Professionals and non-Professionals as a factor which encourages in-group and out-group relations bothering on mutual but manageable intra-organizational strains. Attention has also been directed to the inter-organizational inter-connectedness as a factor which may enhance or inhibit the performance of the judiciary. The third part spells out the procedures involved in adjudication of cases and attempts to relate the theoretical judicial process to judicial process in practice. Marked deviation from the theoretical expectations is observed in practice as a result of the interaction of internal and external forces. The adoption of a social process Orientation lends credence to this Claim. Finally the study raises the issue of the notion of justice; the relationship between the law and the society; and the human Problems in law enforcement.